The effect of indium mole fraction on the growth behavior of inxga1-xas nanowires (NWS) grown using MOCVD - Othaman, Z. (2013)
InxGa1-xAs NWs have been grown with various indium mole fractions (x) using MOCVD. The morphology of InxGa1-xAs NWs was observed using Field Emission-Scanning Electron Microscopy (FE-SEM) in order to study the growth behavior of the NWs. FE-SEM results show that the NWs growth mechanism has changed due to changing of indium mole fraction. At low indium mole fraction, the NWs grew via direct impinging mechanism which has produced NWs with relatively uniform diameter. By increasing the value of x the growth mechanism has transformed to the combination of direct impinging and diffusion of source atoms from the surface of substrate causing tapering of NWs. The degree of tapering increases with increasing value of indium mole fraction. InxGa1-xAs NW grown at x = 0.65 has the highest tapering factor, TF = 12.82, whereas NW grown at x = 0.41 has the lowest tapering factor, TF = 2.76.